Models of Phonological Loanword Adaptation : The Optimality Model as Opposed to the Perceptual and Phonological Models - Abdulrazzaq, Ahmed Hamid; Al-Ubaidy, Sundus Muhsin Ali (Al-Adab Journal, 2023)
Borrowing in linguistics refers to the process whereby a group of speakers incorporates certain foreign linguistic components into their home language via a process known as linguistic borrowing. The process by which these foreign linguistic elements, known as loanwords, go through phonological, morphological, or semantic changes in order for them to fit the grammar of the recipient language is referred to as loanword adaptation. Loanwords go through these changes in order for them to become compatible with the grammar of the recipient language. One of the most divisive topics in loanword phonology is whether adaptations occur at the phonemic or phonetic levels, and current literature distinguishes three primary viewpoints: nativization-through-perception, nativization-through-production, and the Optimality Model. This article provides an overview of lexical borrowing and then presents a detailed account of the three models of phonological loanword adaptation.